PENGUKURAN KUALITAS WEBSITE E-LEARNING SMPN 147 JAKARTA DENGAN METODE WEBQUAL 4.0 DAN REDESIGN WEBSITE MENGGUNAKAN PENDEKATAN UCD - Gelar Asto Bawono (2023)
Information technology has experienced rapid development and has influenced changes in all aspects of life, especially during the COVID-19 pandemic. The role of information technology is highly needed and utilized. In utilizing information technology, SMPN 147 Jakarta has an academic website as a means of online learning. The e-learning site or online media is used for teaching and learning activities at the school. Although the e-learning platform functions well, there are some challenges raised by one of the students, namely the lack of completeness of website features in obtaining information. Additionally, the students also state that although the features are helpful in the teaching and learning process, the website's appearance is not attractive. To assess the quality of the site, the Webqual 4.0 method is used, which consists of three dimensions: usability, information quality, and service interaction quality, with a User-Centered Design (UCD) approach. The researcher will conduct quantitative research using a questionnaire as the research instrument. The selection of respondents will be determined using random sampling technique for the students. Based on the data obtained, the researcher will perform gap analysis, evaluate the webqual index, and use IPA (Importance-Performance Analysis). Based on the data, there are seven indicator variables that require significant improvement, namely US_2, US_4, US_5, US_6, IQ_1, IQ_3, SI_2. After comparing the current system values with the recommended values, it can be concluded that there is an increase in the usability value from 0.57 (Fairly Good) to 0.87 (Very Good), information quality from 0.66 (Good) to 0.87 (Very Good), and service interaction quality from 0.74 (Good) to 0.87 (Very Good).